SHADOW-READING: PROMOTING STUDENTS’ READING COMPREHENSION TO THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT IKIP PGRI BOJONEGORO - Yuniarta Ita Purnama (Jurnal Pendidikan Edutama, 2017)
Abstract: Shadow-reading: Promoting Students’ Reading Comprehension to The First Semester Students of English Department at IKIP PGRI Bojonegoro in The Academic Year of 2016/2017. This research was done to overcome the problem of understanding reading English text so the purpose of the research was to investigate whether the implementation of shadow-reading can promote Students’ Reading Comprehension and to describe the students’ achievement in reading comprehension after taught by using shadow-reading. This was classroom action research in which there were two cycles. The technique of collecting data used triangulation method. It led to seek the validity of the research by collecting information from tests, observations, and interviews. The subject of the research were 32 students of the First Semester at IKIP PGRI Bojonegoro in The Academic Year of 2016/2017. The result showed that the implementation of shadow-reading can promote Students’ Reading Comprehension significantly and students’ achievement in reading comprehension improved effectively in each cycle.Keywords:      Achievement, Comprehension, Shadow-reading.Abstrak: Shadow-reading: Meningkatkan Pemahaman Siswa Terhadap Bacaan (Reading Comprehension) Pada Siswa Semester Satu Program Studi Bahasa Inggris IKIP PGRI Bojonegoro Tahun Ajaran 2016/2017. Penelitian ini dilakukan untuk mengatasi masalah pemahaman siswa terhadap bacaan berbahasa inggris. Tujuan dari penelitian ini adalah untuk menginvestigasi apakah implementasi shadow-reading dapat meningkatkan pemahaman siswa terhadap bacaan dan untuk mendeskripsikan pencapaian (nilai) siswa dalam memahami bacaan setelah diajar dengan menggunakan shadow-reading. Ini adalah penelitian tindakan kelas dengan dua siklus. Tekhnik pengumpulan data menggunakan metode triangulation. Hal ini dilakukan untuk mencari valisitas penelitian dengan mengumpulkan informasi dari tes, observasi, dan wawancara. Subjek penelitian ini adalah 32 siswa semester satu IKIP PGRI Bojonegoro tahun ajaran 2016/2017. Hasilnya menunjukkan bahwa implementasi dari shadow-reading mampu meningkatkan pemahaman siswa terhadap bacaan secara signifikan dan pencapaian (nilai) siswa dalam pemahaman bacaan meningkat secara efektif disetiap siklus.Kata Kunci: Pencapaian (nilai), Pemahaman, Shadow-reading